Weather, macroeconomic variables and stock price in japan - Chai, Kheng Ying (Universiti Malaysia Sarawak (UNIMAS), 2015)
The objective of this study is to investigate the relationship in between impact of weather, exchange rate, fiscal policy, gross domestic product, and interest rate and the stock price in Japan’s primary industry, secondary industry and tertiary industry. The study is conducts for the periods from 2004 until 2013 and the quarterly sample data for the variables are collected. This study employed the Augmented Dickey- Fuller (ADF) Unit-Root Test, Phillip-Perron (PP) Unit Root Test, Johansen and Juselius Cointegration Test, and Granger Causality Test to investigate the relationship among variables. There is a long run relationship in between variables for the Japan’s primary industry, secondary industry and tertiary. Lastly, Vector Error Correction Model (VECM) Granger causality test show the causality relationships occurs in between the variables and LERI, LSPI2 and LSPI3 are solely bears the brunt of short run adjustment to bring the long run equilibrium in Japan’s primary industry, secondary industry and tertiary industry accordingly. From this study, investors need pay more attention on the weather and macroeconomic variables that influence the stock price index in Japan’s stock market.